Diagnostic delay and clinical outcomes of paroxysmal nocturnal hemoglobinuria: a retrospective cohort study using Japanese claims data - Yasutaka Ueda; Tatsuya Kawaguchi; Takayuki Ikezoe; Akihiko Shimono; Hideo Hayashi; Michihiro Uchiyama; Jun-ichi Nishimura; Kaichi Nishiwaki (International Journal of Hematology, 2026)
Abstract Paroxysmal nocturnal hemoglobinuria (PNH) is a rare, potentially life-threatening hematologic disease, often misdiagnosed because of its non-specific symptoms. PNH is characterized by terminal complement activity and intravascular hemolysis, potentially leading to thrombosis, kidney failure, and premature mortality. Early identification remains challenging, necessitating improved diagnostic strategies. In this retrospective JMDC Claims Database analysis, we evaluated the PNH patient journey, including the time from PNH-related symptom onset to first diagnosis and the association of this interval with outcomes. Overall, 160 patients were definitively diagnosed with PNH between July 2010 and April 2022. Flow cytometry (diagnostic standard to detect PNH-type blood cells) was performed in 99 of 160 patients. Ninety-two of 160 patients (57.5%) had PNH-related symptoms before first diagnosis. The median time from PNH-related symptom onset to diagnosis was 26.5 (range, 1–146) months. The incidence of PNH-related complications (kidney failure, thrombosis [including venous thromboembolism]) per 1000 patient-years increased with time from symptom onset to diagnosis. Considerable time elapsed between symptom onset and definitive PNH diagnosis. Longer intervals from symptom onset to diagnosis were descriptively associated with higher rates of complications, including kidney failure and thrombosis, highlighting the potential importance of improved awareness and earlier diagnostic testing for improving PNH outcomes.